DESIGN OF INTEGRATED TRANSPORT SYSTEM (Perner's Contacts, 2008)
Contents of contribution is implementation ones of subsystem of integrated transport system for use Prešov in city and urban traffic. The contribution describes possible computer – aided design of programm AutoCAD 2008 for harmonization of traffic process.
Keywords: transport; integrated transport system; block